Empirical Shear Strength Criterion for Artificial Joint. (May 2019) - Tan, Ran; Chai, Junrui; Cao, Cheng
Abstract: An accurate understanding of shear strength in joints is critical to effective geotechnical engineering. The complete rock shear test continues to shear after shear strength reaches it speak value, resulting in the appearance of a softening stage and a residual stage. Existing research is mainly aimed at the development of dilatancy and shear models of peak strength; few consider post peak processes. This paper attempted to develop a better understanding of changes to shear strength during shear. Direct shear tests of artificial rock joints with the same shape were conducted under the action of 5 normal stresses. By determining a shear dilatancy angle model for the shear process, shear strength can be determined using the Mohr-Coulomb law. The values calculated using our new method agree well with experimental results, indicating that the criterion can be used to accurately estimate the shear strength of rock joints. The parameters required by the proposed criterion can be easily determined in test.